Śūnyamāṃ śabda tuṃ - Joṣī, Dinakara (Pravīṇa Prakāśana, 2012)
Autobiography of Dinakara Joshī, b. 1937, distinguished Gujarati author and critic
In Gujarati-Schr
Keywords: Autobiografie; Joshī; Dinakara; Authors; Gujarati